C-V Calculations in CdS/CdTe Thin Films Solar Cells with a CdSxTe1-x Interlayer - A. Gonzalez-Cisneros; F. L. Castillo-Alvarado; J. Ortiz-Lopez; G. Contreras-Puente (International Journal of Photoenergy)
In CdS/CdTe solar cells, chemical interdiffusion at the interface gives rise to the formation of an interlayer of the ternary compound CdSxCdTe1-x. In this work, we evaluate the effects of this interlayer in CdS/CdTe photovoltaic cells in order to improve theoretical results describing experimental C-V (capacitance versus voltage) characteristics. We extended our previous theoretical methodology developed on the basis of three cardinal equations (Castillo-Alvarado et al., 2010). The present results provide a better fit to experimental data obtained from CdS/CdTe solar cells grown in our laboratory by the chemical bath deposition (for CdS film) and the close-spaced vapor transport (for CdTe film) techniques.